Exergy analysis of vortex tube expansion vapour compression refrigeration system - Sarkar J. (My University, 2025)
Performance comparisons of two vapour compression refrigeration cycles (CYC1 and CYC2) based on the exergetic analysis with three natural refrigerants: ammonia, propane and isobutane are presented using vortex tube as an expansion device. Effects of various operating and design parameters on the performance improvement are presented. Results are shown that the exergetic efficiency improvement over basic expansion cycle increases with increase in cycle temperature lift for both layouts. The exergetic efficiency improvement of CYC1 can be realised for certain operating temperature combinations. Effects of design parameters on the performance improvement are negligible. This study shows that the exergetic efficiency improvement using vortex tube is strongly dependent on the refrigerant varieties, operating conditions as well as cycle configurations. Using the vortex tube as an expansion device, isobutane yields a maximum exergetic efficiency improvement of 12.2% for CYC2 followed by propane (11.5% for CYC2), whereas ammonia yields negligible improvement for studies ranges. Copyright © 2013 Inderscience Enterprises Ltd.